Abscisic Acid Priming Creates Alkaline Tolerance in Alfalfa Seedlings (Medicago sativa L.) - Tian-Jiao Wei; Ming-Ming Wang; Yang-Yang Jin; Guo-Hui Zhang; Miao Liu; Hao-Yu Yang; Chang-Jie Jiang; Zheng-Wei Liang (Agriculture, 2021)
Soil alkalization triggers ion toxicity and osmotic and alkaline (high pH) stresses in plants, damaging their growth and productivity. Therefore, we investigated whether priming with abscisic acid (ABA) increases the tolerance of alfalfa seedlings to alkaline stress, and then examined the underlying molecular mechanisms. Alfalfa seedlings were pretreated with ABA (10 μM) for 16 h and then subjected to alkaline stress using a 15 mM Na2CO3 solution (pH 10.87). Compared with the control, ABA pretreatment significantly alleviated leaf damage and improved the fresh weight, water content, and survival rate of alfalfa seedlings under alkaline conditions. Abscisic acid pretreatment reduced accumulation of reactive oxygen species (ROS), increased activities of the antioxidant enzymes superoxide dismutase (SOD) and peroxidase (POD), maintained higher ratios of K+/Na+, Ca2+/Na+, and Mg2+/Na+, and increased accumulation of proline. In addition, ABA upregulated the expression of genes involved in proline biosynthesis (P5CS) and the sequestration of Na+ in vacuoles (NHX1 and AVP) under alkaline conditions. Abscisic acid priming increased tolerance to alkaline stress by maintaining homeostasis of ROS and metal ions and upregulating osmoprotection and the expression of stress tolerance-related genes.